Dialogue of alternatives between solidarity economy and social economy: The buen vivir concept as decolonial horizon - Ávila Romero, Agustín (Cooperativismo & Desarrollo, 2017)
Purpose: The present work approaches the concepts that revolve around solidarity economy and social economy in different spaces.Themes: In the first place, the concept of solidarity economy and its implications are discussed, then the decolonial processes implicit in the socioeconomic practices of indigenous peoples are considered. The notion of buen vivir (good living) is resumed as an emancipatory proposal that faces the processes of capital valorization, based mainly on dispossession, exploitation and racism.Development: Peasant and indigenous communities of Chiapas, Mexico, maintain socioeconomic and cultural practices that demonstrate principles of reciprocity and redistribution, which confirms that there are other ways of developing economic activities and of relating to nature.Conclusions: Both in the north and global south, alternative socioeconomic processes that are committed to economic solidarity and buen vivir (good living) are put into practice. In the case of Chiapas, Mexico, this dynamic is based on an epistemic and ontological view necessary to observe the breadth of present social experiences.
Keywords: buen vivir (good living); Chiapas; solidarity economy; socioeconomic practices